EXTRACURRICULAR KOLINTANG LEARNING AT SMA NEGERI 2 KEDIRI - bagus sajiwo, daniel (Solah, 2026)
This study aims to describe and analyze the implementation of extracurricular kolintang music learning at SMA Negeri 2 Kediri and to identify the supporting and inhibiting factors in its implementation. The research employed a qualitative approach using a field study method. Data were collected through observation, interviews, and documentation involving the kolintang instructor, students, and school stakeholders. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through credibility, transferability, dependability, confirmability, and data triangulation. The results indicate that extracurricular kolintang learning at SMA Negeri 2 Kediri is implemented through a systematic integration of theoretical instruction and practical activities. The teaching methods applied include lectures, demonstrations, and repetitive practice (drill), adjusted to the types of kolintang instruments and students’ skill levels. The learning process is carried out gradually until students are able to perform kolintang collaboratively in an ensemble. Supporting factors include strong institutional support from the school, high student enthusiasm, and the presence of a competent and consistent instructor. In contrast, inhibiting factors include limited practice time due to academic schedules, a limited number of instruments, and variations in students’ abilities. This study is expected to serve as a reference for the development of traditional music learning, particularly kolintang, within formal educational settings.